Formulasi Kebijakan Kiai Dalam Menguatkan Budaya Literasi di Pondok Pesantren Lirboyo Kediri - Ahmadi, Bagus (Lembaga Penelitian dan Pengabdian Masyarakat IAIN Kediri, 2023)
Kiai policy is an important factor for pesantren to achieve success in strengthening the culture of reading and writing, but it has not been explored in depth about what policies can strengthen the culture of literacy, ideally a policy formulation should be found so that it can be used in general. This study aims to find kiai policies in strengthening the culture of literacy at the Lirboyo Kediri Islamic Boarding School. This research uses a qualitative approach. The type of research design used is field research using a case study design where the subjects studied are leadership and literacy culture at the Lirboyo Kediri Islamic Boarding School. Data collection used were participant observation, in-depth interviews, and documentation. Data analysis was conducted inductively which included data condensation, data presentation, and conclusion drawing. Data validity checks include credibility, dependability, and confirmability. The results of this study indicate that the kiai Policy Formulation in strengthening the culture of reading and writing at the Lirboyo Islamic Boarding School is (1) mahasantri must produce written works resulting from scientific activities and studies of the turast books compiled and analysed based on applicable scientific guidelines and ethics; (2) the discipline of learning in interpreting the contents of the yellow book; (3) Students are required to recite at least one book to the masyayikh and recite one mustahiq according to the book at their level; and (4) Students must record any material taught in class in addition to interpreting the book, write on the Hidayah Mading and Ma'had Aly level